2020
DOI: 10.1108/ecam-01-2020-0042
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the barriers to building information modeling (BIM) implementation within the Nigerian construction industry

Abstract: PurposeThe purpose of this paper is to identify and assess the perceptions of constructional professionals on barriers to implementation of building information modeling (BIM) within the Nigerian construction industry.Design/methodology/approachA scoping literature review was conducted to identify the fourteen barriers to implementation of BIM, which were employed to design a questionnaire survey. Data collected were analyzed using descriptive statistics, mean score, Kruskal–Wallis test, analysis of variance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 71 publications
(107 reference statements)
8
117
1
Order By: Relevance
“…e result coincides with the findings of [41,48,52]. e extent and availability of BIM engineers in the market have been one of the major challenges of BIM Advances in Civil Engineering diffusion in emerging markets, particularly in the African continent [53]. For instance, the study by [34] in Nigeria reported that unavailability of skilled personnel in big construction companies and lack of training for professionals are the obstacles that hinder the adoption of BIM in the construction sector.…”
Section: Discussion and Practical Implicationsupporting
confidence: 84%
See 1 more Smart Citation
“…e result coincides with the findings of [41,48,52]. e extent and availability of BIM engineers in the market have been one of the major challenges of BIM Advances in Civil Engineering diffusion in emerging markets, particularly in the African continent [53]. For instance, the study by [34] in Nigeria reported that unavailability of skilled personnel in big construction companies and lack of training for professionals are the obstacles that hinder the adoption of BIM in the construction sector.…”
Section: Discussion and Practical Implicationsupporting
confidence: 84%
“…is component consists of three BIM adoption attributes: appropriate legal parameters, standards, and guidelines for BIM adoption, and competent consultancy service with factor loadings 0.760, 0.731, and 0.694, respectively. Prior studies reported that lack of standards and specifications is considered as the major hindrance of BIM implementation and diffusion in emerging markets [53,55].…”
Section: Component IImentioning
confidence: 99%
“…Olugboyega (2016) acknowledged the vital role played by BIM in EAC project as it ensures that all aspect of the project was fully captured without omissions. BIM is a significant tool in the enhancing lifecycle and knowledge sharing in the construction project (Olanrewaju et al, 2020). Despite this importance, BIM is yet to be fully implemented in most construction projects as Anifowose et al (2018) recorded a 40% level of awareness.…”
Section: Bim-compliant Software Used By Professionalsmentioning
confidence: 99%
“…e global construction industry is currently evolving due to the introduction of new technological advancements and innovations [1,2]. is rapid growth can be realized in the adoption of Building Information Modeling (BIM) in highvalue infrastructure projects across the construction sector [3]. BIM has been understood as an information technology (IT)-driven innovative process integrating certain features, disciplines, and life-cycle information of a facility within a single working platform [4].…”
Section: Introductionmentioning
confidence: 99%